Pengembangan Sistem Informasi Geografis Untuk Inventarisasi Seni Dan Ritus Menggunakan Metode Addie (Studi Kasus: Kecamatan Pupuan, Tabanan) - Ni Putu Dinda Srirasita; I Putu Mahendra Adi Wardana; Kadek Oky Sanjaya (Program Studi Sistem Informasi, Fakultas Teknologi Informasi dan Sains, Universitas Hindu Indonesia, 2026)
Bali is one of the provinces in Indonesia that possesses a unique and diverse cultural heritage across its regions. This culture serves as a vital asset for tourism and national identity. However, amidst modernization and globalization, cultural preservation faces significant challenges. Pupuan District, as part of Tabanan Regency, has a variety of arts and rituals that need to be systematically documented to prevent them from being forgotten. This study aims to develop a web-based Geographic Information System (GIS) to inventory the arts and rituals in Pupuan District, Tabanan. The research utilizes the ADDIE method, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The system is developed using the Laravel 11 framework, PHP 8.2, and Leaflet for interactive mapping, with MySQL as the database to store cultural information. The research findings indicate that this system facilitates stakeholders in accessing cultural information through a website equipped with interactive features. The system testing was conducted using the blackboxtesting method, and the results showed that the system operates optimally according to user requirements.